Integrating traditional farming practices in forest management unit 11 for sustainable forest landuse - Mandy Maid; John Tay; Hardawati Yahya (Universiti Malaysia Sabah, 2010)
The evolving traditional agricultural practices by rural communities necessitate the adoption of agroforestry practices to improve community livelihood and to support the control of illegal encroachment A community of 22 families from 14 households living within the Community Forestry Zone (CFZ) of the Ulu Sg. Milian Forest Reserve was chosen as the interest group. The method used in this study is Rapid Rural Appraisal (RRA) which included face-to-face interviews and a dialogue session to gather information about socia-economic, agriculture practices and community perception on agroforestry practiCes. The findings conclude that historical chronology of forest condition and forest management activities is related to forest policy changes. Community settlement and activities in the forest reserve (FR) depended on access road introduced by commerdal logging. The change in farming practices was driven by economic factors and forestry poliCies. Village area profiled in a historical transect shows the physical changes of farming area and infrastructure from 1980s to 2010. Majority of the community view rubber-based agroforestry in cooperation with forest managers poSitively. However, all stakeholders must reach a consensus on the terms and conditions of the program. The changing agricultural practices were driven by community's effort to secure land tenure rights, economiC pressure, deteriorating environmental conditions and state govemment poliCies that promoted sustainable forest management. Varying combinations of agroforestry should be promoted to achieve socio-economic improvement and control of illegal encroqchment.